Odpowiedź :
Odpowiedź:
a)
-24√(5 1/16) + 12 * ∛(3 3/8) - 15 * √(2 14/25) = -24√81/16 + 12∛27/8 - 15√64
= -24 * 9/4 + 12 * 3/2 - 15 * 8 = -54 + 18 - 120 = -36 - 120 = -156
b)
9 * ∛8/27 - 20 * √(1 9/16) + 4 : ∛64/125 = 9 * 2/3 - 20√25/16 + 4 : 4/5 =
= 6 - 20 * 5/4 + 4 * 5/4 = 6 - 25 + 5 = 6 - 20 = -14
c)
(-1/2)³ * √(7 1/9) - ∛(4 17/27) * (-1,8)² - 2²/15 = -1/8 * √64/9 - ∛125/27 * 3,24 -
- 4/15 = -1/8 * 8/3 - 5/3 * 3,24 - 4/15 = -1/3 - 324/100 - 4/15 = -5/15 - 4/15 - 81/25 = -9/15 - 3 6/25 = -3/5 - 3 6/25 = -15/25 - 3 6/25 = -3 21/25
d)
√[15 * √(45√25)] - ∛[27 * ∛(256 * ∛8)] = √[15 * √(45*5)] - ∛[27 * ∛(256 * 2)] = √(15 * √225) - ∛(27 * ∛512) = √(15 * 15) - ∛(27 * 8) = 15 - ∛216= 15 - 6 = 9
Szczegółowe wyjaśnienie: